Gender Roles and Changing Pattern on Baram Community: An Ethnography From Chandipurnima Festival (Research Nepal Journal of Development Studies, 2019)
Second generation of women of Baram Community is highly constructive in social norms, values, customs, and tradition and very sensitive in gender equality than first generation. The major issue of this study is to find out the gender roles of Baram community from a major festival - Chandipurnima. The nature of gender roles and changing pattern on festival between two generations among Baram community, sharing behavior during the festival, power relation between male and female has been addressed. There are vast differences on two generations regarding the gender roles, first generation is still traditional and believe on radical cultural practices where as new generation has the impact of modernity and change due to the education and labor migration. However new generation is found high alert in social identity and cultural practices of the community. As it is an ethnography the study has been conducted based on participant observation and interview on the special occasion of celebration of Chandipurnima of Baram Community of Gorkha.